1979
DOI: 10.1111/j.1399-3054.1979.tb06517.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulphur Dioxide on Sugar and Free Amino Acid Content of Pine Seedlings

Abstract: Treatment of jack pine (Pinus banksiana Lamb.) seedlings with gaseous SO2 resulted in a shift between the reducing and non‐reducing sugars. Increasing concentrations of gaseous SO2 caused an increase in reducing sugars and a decline in the non‐reducing sugars, suggesting a conversion from the latter to the former at high SO2 concentrations. The total amino acid content of the intact tissues also increased with increasing concentrations of gaseous SO2. Gas‐liquid chromatographic analyses of the amino acids indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(32 citation statements)
references
References 17 publications
2
27
1
2
Order By: Relevance
“…Accumulation of reducing sugar and depletion of starch were reported in Mangifera indica and Psidium guajava growing under pollution stress (Kumar & Singh 1988). Increase in reducing sugars and decrease in non-reducing sugars oc-curred in pine seedlings as a result of SO 2 pollution (Malhotra & Sarkar 1979). Sugar level in the roots of pollution-affected P. bicalyculata was low, marginally at the pre-flowering stage and significantly during the later stages.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Accumulation of reducing sugar and depletion of starch were reported in Mangifera indica and Psidium guajava growing under pollution stress (Kumar & Singh 1988). Increase in reducing sugars and decrease in non-reducing sugars oc-curred in pine seedlings as a result of SO 2 pollution (Malhotra & Sarkar 1979). Sugar level in the roots of pollution-affected P. bicalyculata was low, marginally at the pre-flowering stage and significantly during the later stages.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported degradation of membrane lipids with possible hydrolysis of proteins inducing quantitative changes in amino acid composition and an increase in reducing sugars prior to the appearance of visible symptoms (Malhotra & Sarkar 1979). Variations due to environmental stress in the biochemistry of plant tissues are little explored in relation to the growing age of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Method of 5,6,7 were used for estimation of total soluble sugar, reducing sugar and non-reducing sugar . The total soluble protein was estimated using Lowery et al, 1951 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Gly and Ser, both related to glycerate-3-phosphate, stand in direct relation to each other. Malhotra & Sarkar (1979) reported conversion of Ser to Gly after SOj fumigation. In our investigations however Gly and Ser did not show any clear fluctuations.…”
Section: Tke Variation Of Amino Acids Due To Different Mtrogen Pollutionmentioning
confidence: 99%